(untitled) (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2022)
The significance of the technology for the development of critical thinking is revealed, the methodological conditions for its formation are determined, and the most effective methods for the development of critical thinking in the lessons of the Russian language and literature are proposed.